Quality Characteristics and Acceptability of Three Types of Pitaya Fruits in a Consumer Acceptance Test / Chemah Tamby Chik …[et al.] - Tamby Chik, Chemah; Bachok, Sabaianah; Baba, Noradzhar; Abdullah, Aminah; Abdullah, Noriham (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2011)
Three types of pitaya fruits Hylocereus polyrhizus, Hylocereus undatus and Selenicereus megalanthus were subjected to colour evaluation, proximate test, physicochemical analysis and consumer acceptance test. Morphologically, red pitaya have red violet pulp while white pitaya and yellow pitaya both have white pulp. The other significant difference is the peel colour; yellow pitaya are differentiated from the other two pitaya by their significant yellow peel as compared to red and white pitaya which have red peel. L, a* and b* values for the pitaya pulp are 25.3, 27.8 and -1.1 for red pitaya, 54.9, 0.5 and 2.3_ for white pitaya and 21.9, 30.9 and -2.1 for yellow pitaya. Red pitaya peel had 37.9, 40.0 and 10.7 for its L, chroma and hue value. Seeds contained the highest protein andfitt (p < 0.05) with value of 23.1 to 28.6% and 18.8 to 22.8% respectively. Pitaya peel contained the highest ash content ranging from 15 to 28.8% while pulp contained the highest carbohydrate ranging from 86.3 to 90.6%. pH value for pitaya fruits pulp and peel range between 4.6 to 4.7 and 5.3 to 5.5. White pitaya pulp showed significant (p < 0.05) titratable acidity with 26.8 g/L while red and yellow pitaya had 19.3 g/L and 17.9 g/L respectively. Hedonic sensory analysis indicated that red pitaya was preferred in terms of its sweetness and overall liking. Red pitaya fruit showed potential to be developed into other food products due to its distinct red colour and was the most preferred choice in overall sensory hedonic tests.